Curcumin: Towards molecularly targeted chemoprevention of cancer. Issue 2 (January 2015) - Pfeffer, Ulrich; Amaro, Adriana; Bachmeier, Beatrice; Angelini, Giovanna
Abstract: Everybody is at risk for cancer yet environmental factors, lifestyle and diet as well as genetic factors influence the individual cancer risk. Targeted or personalized cancer prevention is based on the knowledge of the molecular characteristics of the tumor to be prevented, the molecular mechanisms of action of the compounds to be used and the genetic make-up of the person who opts for prevention medicine. Genetic factors are to a certain extent specific for cancer types or even subtypes as it has been shown for breast cancer. The growing knowledge of such genotype cancer risk associations will allow for the definition of personalized prevention strategies. Prevention in intermediate risk populations requires non-toxic, well tolerated and cheap compounds. The main activity of the polyphenol Curcumin is the inhibition of nuclear factor kappa B (NFkB) activation. NFkB is involved in many cancers where it acts through the generation of chronic inflammation that can be contrasted by the anti-inflammatory activity of Curcumin. Curcumin mediated inhibition of NFkB leads to the interruption of a pro-metastatic positive feedback loop where NFkB induces the expression of inflammatory cytokines which in turn promote NFkB activation and the transcription of NFkB regulated pro-metastatic factors such as COX2, SPARC, ALDH3A1 and EFEMP1. By interrupting this loop Curcumin significantly reduces the formation of metastases in murine breast and prostate cancer models. Clinical trials for primary prevention must rely on a risk based selection of participants and well characterized response markers. Targeted cancer prevention can be applied as primary prevention, after diagnosis in low risk situations where watchful waiting could be integrated by prevention drugs and after adjuvant therapy to contrast the remaining risk of relapse. Adequately targeted, cancer prevention approaches are expected to outperform the effects of current cancer therapy in terms of overall survival.